2014
DOI: 10.1002/ptr.5202
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Standardized Extract of Ziziphus jujuba Fruit (Jujube) Stimulates Expressions of Neurotrophic Factors and Anti‐oxidant Enzymes in Cultured Astrocytes

Abstract: quinine oxidoreductase 1, glutamate-cysteine ligase catalytic subunit, glutamate-cysteine ligase modifier subunit and glutathione S-transferase, in a concentration-dependent manner. These results proposed the benefits of jujube in regulating expressions of neurotrophic factors and anti-oxidant enzymes in cultured astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Calculation was done by using Ct value of 18S of normalize Ct value of target gene in each sample to obtain ΔCt value, which then was used to compare among different samples. PCR products were analyzed by melting curve analysis to confirm specific amplifications [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Calculation was done by using Ct value of 18S of normalize Ct value of target gene in each sample to obtain ΔCt value, which then was used to compare among different samples. PCR products were analyzed by melting curve analysis to confirm specific amplifications [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the upregulation of neurotrophic factors can play a positive role in treating neurological diseases. The effect of jujube on neurotrophic factor expression was investigated in cultured astrocytes [16]. The treatment with jujube water extract stimulated the expression of neurotrophic factors in a dose-dependent manner, having the highest induction of ~100% for NGF, 100% for BDNF, 100% for GDNF, and 50% for NT3.…”
Section: Jujube On Neuron Differentiationmentioning
confidence: 99%
“…Besides, the application of jujube water extract could stimulate the transcriptional activity of CRE. Further studies also showed that pretreatment with H89 significantly blocked jujube-induced neurotrophic factors including NGF, BDNF, and GDNF, indicating the possible involvement of PKA signaling in jujube-induced neurotrophic factor expression [16]. …”
Section: Jujube On Neuron Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we have verified the hematopoietic function of jujube by regulating EPO expression via hypoxia‐inducible factor‐1α in liver cells (Chen et al , ). Thus, the production of EPO will further trigger the formation of RBC.…”
Section: Discussionmentioning
confidence: 99%